Abnormal eye movements in parkinsonism: a historical view - Ko, Tereza; Brenner, Augusto Mädke; Monteiro, Nicholas Pili; Debastiani, Mariana Severo; Nesello, Alberto Chitolina; Hilbig, Arlete (Arquivos de Neuro-Psiquiatria, 2021)
Parkinson's disease (PD), known since ancient times as paralysis agitans, was studied and described by James Parkinson in 1817 in his work “An Essay on the Shaking Palsy”. Fifty years later, Charcot and his students delved into the disease, naming it as we know it today, as well as defining the classic disease and its variants. One of these students, Arthur Dutil, addressed patients’ abnormal eye movements. Nowadays, it is known that the differential diagnosis of PD is relevant for prognosis, treatment and research, and, despite the advances in the area, it remains largely clinical. The relevance of the eye movement exam has grown along with the history of PD and it has proved to be an excellent tool for the differential diagnosis of parkinsonism. Additionally, it can become a support to identify different types of genetic PD and be useful for improving early recognition of cognitive decline in patients with PD.
Keywords: Eye Movements; History of Medicine; Parkinson Disease; Parkinsonian Disorders